Explorations and entanglements : Germans in Pacific Worlds from the early modern period to World War I - Berghoff, Hartmut; Biess, Frank, 1966-; Strasser, Ulrike, 1964- (Studies in German history ;, 2019)
"Traditionally, Germany has been considered a minor player in Pacific history: its presence there was more limited than that of other European nations, and whereas its European rivals established themselves as imperial forces beginning in the early modern era, Germany did not seriously pursue colonialism until the nineteenth century. Yet thanks to recent advances in the field emphasizing transoceanic networks and cultural encounters, it is now possible to develop a more nuanced understanding of the history of Germans in the Pacific. The studies gathered here offer fascinating case studies of German missionary, commercial, scientific, and imperial activity against the backdrop of the Pacific's overlapping cultural circuits and complex oceanic transits"--